Central muscarinic receptors signal pilocarpine-induced salivation - Takakura, ACT; Moreira, T. S.; Laitano, S. C.; De Luca, L. A.; Renzi, Antonio [UNESP]; Menani, José Vanderlei [UNESP] (Sage Publications Inc, 2003)
Although cholinergic agonists such as pilocarpine injected peripherally can act directly on salivary glands to induce salivation, it is possible that their action in the brain may contribute to salivation. To investigate if the action in the brain is important to salivation, we injected pilocarpine intraperitoneally after blockade of central cholinergic receptors with atropine methyl bromide (atropine-mb). In male Holtzman rats with stainless steel cannulas implanted into the lateral ventricle and anesthetized with ketamine, atropine-mb (8 and 16 nmol) intracerebroventricularly reduced the salivation induced by pilocarpine (4 mumol/kg) intraperitoneally (133 +/- 42 and 108 +/- 22 mg/7 min, respectively, vs. saline, 463 +/- 26 mg/7 min), but did not modify peripheral cardiovascular responses to intravenous acetylcholine. Similar doses of atropine-mb intraperitoneally also reduced pilocarpine-induced salivation. Therefore, systemically injected pilocarpine also enters the brain and acts on central muscarinic receptors, activating autonomic efferent fibers to induce salivation.
Keywords: muscarinic receptors; acetylcholine; atropine; salivary glands; parasympathetic